Maturidade do ecossistema de startups na cidade de João Pessoa - Vieira, Mateus Lima (2019)
Entrepreneurs and their startups have drawn the attention of many researchers and organizations for their ability to revolutionize markets and to promote the “creative destruction” on a never before seen scale. However, the major prominence in the discussions on socioeconomic development in political and business contexts has been the concept of entrepreneurial ecosystem or startups ecosystem. This approach emphasizes how the connection between actors established in the formal and informal institutions that belong or serve a particular region, sustain the entrepreneurial activity of startups in that place through continuous processes of development and flow of resources over time. This work presents an analysis of the startups ecosystem maturity in João Pessoa. The research, of an applied, qualitative and exploratory nature, constitutes a case study whose method for data collection was the semi-structured interview conducted with 20 (twenty) respondents among entrepreneurs, mentors, investors, members of support organizations, universities and technology companies, whose analysis was based on content analysis and the application of the software startups ecosystem maturity model. In this way, it was possible to verify that startups ecosystem of João Pessoa is nascent, mainly marked by the absence of a culture that encourages connections between local actors. From the analysis, it was also possible to identify critical factors of the current ecosystem maturity level, such as the promotion of entrepreneurship in universities, the establishment of connections between actors and the lack of angel investors. As well as some proposals for action (drivers) to local actors, such as joint actions of all key actors, formation of an investors group and the startups mapping. Likewise, the startups ecosystem of João Pessoa was compare with Tel Aviv, São Paulo and New York - locations already examined by the same maturity model adopted in the study. Unlike these other environments, are the support organizations like Sebrae Paraíba through its pre-acceleration program (StartPB), local coworkers and FabWork rather than the Government or the startup entrepreneurs themselves who have been the main promoters of the ecosystem in João Pessoa. In the midst of a specific social, political, economic, cultural and geographic context, João Pessoa's startups ecosystem needs entrepreneurs who take the lead and seek development with the resources and capabilities they possess.